The Changing Trend in Clinical Characteristics and Outcomes of Male Patients With Urethral Stricture Over the Past 10 Years in China - Cheng, Xu; Ding, Mao; Peng, Mou; Zhou, Lizhi; Li, Yijian; Peng, Shuang; Cheng, Shunhua; Wang, Yinhuai (Frontiers in Public Health, 2021)
Background: Male urethral stricture is a disease with high incidence rate. With social-economic development in the developing countries, the trend of etiology and treatment of male urethral stricture changed was speculated. Methods: the clinical data of the male patients with urethral stricture from 2000 to 2019 were analyzed retrospectively. The subjects were divided into Group A (2000-2009) and Group B (2010-2019) according to treatment time. The pooled analysis of the data extracted from literatures was also performed. Results: 540 patients were included in the present study, including 235 patients in Group A and 305 patients in Group B. In recent 10 years, trauma is still the main cause of urethral stricture. Iatrogenic injury, especially transurethral operation increases significantly, while causes of radiotherapy and infection decreases. Urethroplasty increases and the reoperation rate decreases in treating simple urethral stricture, and flap urethroplasty also increases in treating complex urethral stricture. The results of pooled analysis of data from 11 centers in Mainland China is partially consistent with it. Complications, such as urethral fistula, false canal, ejaculation disorder and penile curvature decreases significantly. Conclusions: The main cause of urethral stricture in the recent 10 years are still trauma and iatrogenic injuries, and etiology of urethral stricture is related to socio-economic development. With the increase of intracavitary minimally invasive treatment and flap urethroplasty, the curative effect is increasing, while iatrogenic urethral stricture cannot be ignored.